Pengaruh Dukungan Manajemen Puncak dan Komunikasi Pemakai-Pengembang terhadap Hubungan Partisipasi dan Kepuasan Pemakai dalam Pengembangan Sistem Informasi - Sunarti Sunarti Setianingsih; Nur Indriantoro (The Indonesian Journal of Accounting Research, 2013)
The importance of user participation to improve user satisfaction in the systems development process has been widely recognized in the literature. However, the perspective has suffered from equivocal results of empirical test and the absence of a theoritical explanation for the relationship. The purpose of this study is to investigate the interaction effect of contigency factor — top management support and user-developer communication — on relationship between user participation and user satisfaction. As suggested in the literatur, this study test hypotheses that these specific contigency factors should aid in indentifying situation where user participation would have a strong relationship with satisfaction.This study based on the responses of 94 midle manager from different organizations. The result of the analysis indicated that user participation has a direct relationship with user satisfaction. In addition, the contingency factors were found to play key roles on this relationship. Top management support proved to be quasi moderator. In project where there was a high level of top management support, the relationship between user participation and user satisfaction was significantly stronger than in project where top management support was low. User-developer communication were shown to be independent predictor of user satisfaction. User developer communication was positively related to user satisfaction regardless of the level of participation.The result have implications to systems developers and to academicians seeking to explain how, when, why and where user participation is needed. It was also explained the relationship between user participation and user satisfaction by suggesting the nature of relationship under different sets of conditions. Keywords: User participation, user satisfaction, top management support, user-developer communication.